Permanent Congenital Hypothyroidism due to Rare Thyroglobulin Gene Variant (p.Cys1476Arg): A Delayed Diagnosis of Thyroid Dyshormonogenesis - Ghassan Mohamadsalih; Khalid Al Bureshad; Idris Mohammed; Shiga Chirayath; Elwaseila Hamdoun; Khalid Hussain (Case Reports in Medicine)
Thyroid dyshormonogenesis is an inherited hypothyroidism caused by a monogenic defect, in the vast majority of cases, in thyroid hormone biosynthesis. It is commonly associated with thyroid enlargement which is vulnerable to nodule formation. We present a Qatari patient with an overlooked diagnosis of thyroid dyshormonogenesis due to thyroglobulin gene mutation. A 10.5-year-old boy has been following up for congenital hypothyroidism since the age of 4 years. He was diagnosed by newborn screening that was confirmed by laboratory thyroid function testing; however, no further workup was done to understand the underlying cause. He was born to consanguineous parents with a family history of hypothyroidism. The patient was not adherent to his medication and follow-up visits, and thyroid-stimulating hormone was above 5 mIU/L most of the time. On examination, he had a goiter that developed a few months ago. The father admitted that it was there at birth but disappeared with levothyroxine therapy. Molecular genetics revealed a homozygous c.4426T > C, p.Cys1476Arg variant in the thyroglobulin gene. This variant was only previously reported, in the Middle East region, in five patients. Determination of congenital hypothyroidism underlying etiology is important for family counseling and long-term management.